Factors Associated With Stunting Incidence Among Children Aged 0–59 Months In The Working Area Of Kilasah Public Health Center, Serang City, Indonesia, 2023 - Sadya Bustomi; Mukhlasin Mukhlasin; Yenyen Yuliana (Journal of Social Research, 2025)
Stunting is a condition of failure to thrive in children due to chronic malnutrition from the age of 0–59 months, which is marked by a nutritional status index (PB/U) or (TB/U) with a Z-Score of less than -2 SD, which results in a child's height not being according to his age. The working area of the Kilasah Health Center has been the LOKUS (Focus Location) of stunting until now because it still contributes to a fairly high number of cases. This study aims to determine the factors associated with the incidence of stunting in children aged 0–59 months in the work area of the Kilasah Health Center, Serang City, in 2023. The method used is an observational study with a case-control approach. The instruments used were questionnaires and observation sheets. The research sample consisted of two groups, namely the case group of 44 respondents and the control group of 44 respondents, which were taken by the purposive sampling technique. The results of the univariate test in the stunting toddler group showed that the mothers had poor knowledge of 84.1%, 88.6% did not exclusively breastfeed, 36.4% did not have healthy latrines, and 93.2% did not have clean water facilities that met the requirements. Bivariate analysis using Chi Square obtained the results that mother's knowledge (Pv = 0.000), exclusive breastfeeding (Pv = 0.000), healthy latrines (PV = 0.000), and clean water facilities (Pv = 0.0013) have a significant relationship with the incidence of stunting in children aged 0-59 months. The suggestion from this research is that it is necessary to increase counseling with booklets/flip sheet regarding stunting and the importance of nutritious food for toddlers.